Diga ao povo que FICA: educação ambiental e difusão audiovisual no Festival Internacional de Cinema e Vídeo Ambiental (1999-2022) - (:unkn) unknown (Universidade Estadual de Goiás, 2022)
The International Environmental Film Festival (FICA) emerged in 1999, as a government project aimed at promoting culture, especially in the audiovisual segment, in the state of Goiás. However, the environmental motto, which names the event, has raised questions about its efficiency and didactic usefulness among many researchers and critics. On this basis, the objective of this dissertation was to reflect on how FICA collaborates with the ideals of Environmental Education, starting from the investigation of the political and cultural context that conceived it, characterizing the matrices of environmental thinking, as well as the external movements that guide the environmental policies in which the festival is limited. In analyzing the didactic potential of film works, a semiological approach is adopted, supported by the historiography of Goiás and Brazil. This work used qualitative research resources, such as interviews and the analysis of many informative and documentary pieces that took care of the presentation of the 23 editions of the respective shows. The research contributed to the historiographical update of FICA, describing its political dynamics from 2019, the year of suspension, and the most held in 2020, 2021 and 2022 that comprise the adaptation and resumption of what has been consolidated as the biggest event of environmental cinema in Latin America. The field research also verified that the particular strategies of dissemination of FICA, in addition to characterizing actions of democratization of access to environmental contents, are pedagogically opportune to the Basic Education curriculum.
Say to the people that FICA: environmental education and audiovisual dissemination at the International Environmental Cinema and Video Festival (1999-2022)
Keywords: Educação ambiental - FICA - Cidade de Goiás; Educação ambiental - Cine Goiás Itinerante - Cidade de Goiás; Educação ambiental -Audiovisual e cinema ambiental - Cidade de Goiás; CIENCIAS HUMANAS::EDUCACAO; ARTES::CINEMA